2007
DOI: 10.1002/app.26093
|View full text |Cite
|
Sign up to set email alerts
|

Chitin sponge, extraction procedure from shrimp wastes using green chemistry

Abstract: Chitin sponges were obtained from shrimp residues using green chemistry procedures. Partial deproteinization was performed by grinding fresh residues with water during 30 s in a food blender obtaining 39.3% d.b. partial deproteinized cephalothorax (PDC). Protein reduction in this step was 80%, with 49% of mineral salts (measured as ashes), 97% fat, and 41% being chitin product. To separate chitin from PDC, a mixture of 8.75 mL MeOH, 16.25 mL water, and 25 g of CaCl 2 was used (solvent MAC) per gram of PDC. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
5
0
3
Order By: Relevance
“…The mixed composts made of crab or shrimp wastes used in our study originally contained chitin, which could hardly be classified in a biochemical fraction using the NDF-ADF-ADL procedure. Chitin is a poly (N-acetyl-D-glucosamine) insoluble in water and in most organic solvents because of strong H bonds between polymer chains (Flores et al 2006). However, the oligomeric chitin formed during composting is water soluble and easily hydrolyzed (Roy et al 1997;Labrie et al 2001).…”
Section: Sample Preparation and Analysesmentioning
confidence: 99%
“…The mixed composts made of crab or shrimp wastes used in our study originally contained chitin, which could hardly be classified in a biochemical fraction using the NDF-ADF-ADL procedure. Chitin is a poly (N-acetyl-D-glucosamine) insoluble in water and in most organic solvents because of strong H bonds between polymer chains (Flores et al 2006). However, the oligomeric chitin formed during composting is water soluble and easily hydrolyzed (Roy et al 1997;Labrie et al 2001).…”
Section: Sample Preparation and Analysesmentioning
confidence: 99%
“…Por lo tanto, métodos de extracción verde son empleados debido a su naturaleza respetuosa con el ambiente. Dentro de este grupo se encuentran los procesos de extracción enzimáticos (Lopes et al, 2017;Younes et al, 2014) y procesos donde el uso de ácidos y álcalis son remplazados por solventes menos drásticos (Flores et al, 2007;Tolesa et al, 2019). En este sentido, Barrera-Rodríguez et al (2011) y Flores-Ortega et al (2006, obtuvieron películas y esponjas de quitina a partir de residuos de camarón usando un disolvente compuesto por metanol, agua y cloruro de calcio para sustituir el uso de HCl y NaOH en los procesos de desmineralización y desproteinización.…”
Section: Introductionunclassified
“…28 It was shown that chitin is soluble in 9% solution of lithium chloride in 1-methyl-2-pyrrolidinone (NMP) or N,N-dimethylacetamide (DMAc). 31 Moreover, it has to be pointed out that chitin is very often confused with chitosan; indeed, chitosan is prepared by deacetylation and depolymerisation of native chitin, however, one cannot consider these compounds as substitutes and should recognize chitosan as soluble derivative of chitin. Destabilized intra-and inter-molecular hydrogen bonds result in a change of chitin crystalline structure and make it soluble in Li + /NMP solution.…”
Section: Introductionmentioning
confidence: 99%